Understanding the Reasons for the Establishment of Small Tea Garden- an Enquiry Across the Sub-Himalayan Northern Tracts of West Bengal - Ashad, Rahul; Das, Kalyan Kanti; Kar, Shouvik; Roy, Pritam (International Journal of Bio-resource and Stress Management, 2026)
The present study was conducted during August, 2024 to January, 2025 to explore reasons behind the establishment of Small Tea Gardens (STGs) across the subHimalayan northern tracts of West Bengal. Primary data were collected from 180 STG households distributed over three districts, six blocks, and twelve villages using stratified random sampling and pretested questionnaires. Perceptions were measured on a fourpoint Likert scale. Interdistrict variation in perceptions was assessed with Kruskal–Wallis statistics followed by Dunn’s posthoc tests. About 79% of the STG community have more than 20 years of farming experience and 72% belong to backward caste groups. These smallholding farmers, with an average net cultivated area of 1.76 ha, allocate about 24% of their land to STGs. Land conversion patterns show that about 32% of STGs utilize fallow land, 28% replaced paddy fields, and 21% replaced wheat fields. Economic factors like notably relative profitability and assured, reasonable price realization emerged as key drivers for establishing STGs. Technical factors, including congenial soil and favorable weather conditions, and social factors, such as womenfriendly cultural practices and proximity to boughtleaf factories, also played crucial roles in decisionmaking. Significant interdistrict variations were observed across these factors. Based on the findings, the study recommends policy interventions focused on infrastructure development, targeted training, and strengthened linkages with relevant organizations and associations to support sustainable expansion and improved livelihoods among small tea growers.